Organologi Selober pada Sanggar Selober Pejenengan Desa Pengadangan Pringgasela Lombok Timur - Baha, M Abdi; Murcahyanto, Hary; Imtihan, Yuspianal (Universitas Hamzanwadi, 2020)
This paper aims to describe and describe the organology of a traditional musical instrument as seen from its physical classification at the Selober Pejenengan Studio in the Village of Inflation in the Pringgasela District, East Lombok using organology theories. The approach used in this research is descriptive qualitative. From the results of the study found about: 1) organology and the process of making a traditional musical instrument as follows, consisting of: the level of dryness, the process of selecting materials, the process of contracting, the process of making tongue lines, the process of making the head and feet of musical instruments, and the refinement process. 2) the production of tones on a traditional musical instrument that consists of tones produced by Selober Mame and Selober Â nine.